Investigating the strategy of successful businesses in the Corona crisis - MolkAra, Melika (International Journal of Business Management and Entrepreneurship, 2022)
The earliest movement which is required to be considered during a crisis is grasping the existing circumstances. Crises in business are not exempt from this rule. Principally, precise, accurate grasping and realization of any dilemma will be half of the solution. The alternative significant technique that companies have changed their business models is through enlarging the magnitude of cooperation between competing organizations. Even policy makers are involved in competing activities due to the impact of this pandemic and necessity to stable economic and sanitary objectives. Some businesses have been able to achieve success by setting up an online shops and producing contents and measures which will be discussed in present paper.